2022
DOI: 10.1002/jhbp.1206
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with robotic liver resection: Audit of 120 consecutive cases at a single center and comparison with open and laparoscopic approaches

Abstract: Background/Purpose: Surgical outcomes and utility of robotic liver resection (RLR) are undefined. Methods: We retrospectively studied perioperative and long-term outcomes of the single-center 120 RLRs including non-anatomic (NAR, n = 58) and anatomic (AR, n = 62) resections. To evaluate the feasibility and safety of RLR, perioperative outcomes of RLR (n = 103) were compared to those of open (OLR, n = 495) or laparoscopic (LLR, n = 451) resection in liver-only resections without reconstruction, using 1:1 propen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…As for technical aspects of MIAR, we believe, from the current and previous results, that we can standardize MIAR by using the extrahepatic Glissonian approach and HV root-at first one-way parenchymal dissection [ 4 , 5 , 6 , 13 , 18 , 19 , 23 ]. Furthermore, the consistent usage of these standardized techniques, irrespective of OAR and MIAR, may reduce technical biases, being an advantage of this study setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for technical aspects of MIAR, we believe, from the current and previous results, that we can standardize MIAR by using the extrahepatic Glissonian approach and HV root-at first one-way parenchymal dissection [ 4 , 5 , 6 , 13 , 18 , 19 , 23 ]. Furthermore, the consistent usage of these standardized techniques, irrespective of OAR and MIAR, may reduce technical biases, being an advantage of this study setting.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies comparing open and minimally invasive liver resections have shown less blood loss, decreased morbidity, and shorter LOS in the latter [ 23 , 26 , 27 , 28 , 29 ]. Laparoscopic and robotic liver resections were shown to have comparable perioperative outcomes [ 23 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…)-guided small anatomical resection[ 38 ], indocyanine green (ICG)-guided anatomical resection and tumor identification[ 39 ], and LLR with a Glissonian approach to more peripheral smaller branches from the hilum (cone unit resection)[ 40 ]. Robot-assisted LLR is an important emerging tool under discussion[ 25 , 41 ]. It could be advantageous, for example, in cases exposing a wide range of Glissonian pedicles and major hepatic veins.…”
Section: Minimally Invasive Liver Surgerymentioning
confidence: 99%
“…This method devised by Makuuchi is widely used in open surgery [1] , but it poses significant difficulties or needs special expertise in MIS because of technical or instrumental insufficiency [11] . The other is the conventional "negative-coloring method" without the use of dye or the "negative-staining method" which visualizes the target segment as a negatively stained area through systemic injection of indocyanine green (ICG), after occluding the target segmental GPs that are isolated intrahepatically or extrahepatically [8][9][10][12][13][14][15] . Recent technical refinements in isolation of segmental GPs, as well as advances in fluorescence navigation technology, have promoted the application of the negative-staining method in open and minimally invasive IA-Seg.…”
Section: Introductionmentioning
confidence: 99%